Patient care under uncertainty - Manski, Charles F. (Princeton University Press, 2019)
"Although uncertainty is common in patient care, it has not been largely addressed in research on evidence-based medicine. Patient Care Under Uncertainty strives to correct this huge omission. For the past few years, renowned economist Charles Manski has been applying the statistical tools of economics to decision making under uncertainty in the context of patient health status and response to treatment. In the precise language of econometrics, "uncertainty" means that the available evidence and knowledge do not suffice to yield precise probabilistic predictions. In the health-care sphere, the most common example is a choice between periodic surveillance or aggressive treatment of patients at risk of a potential disease. Manski examines the subject by applying the economic principals of personalized risk assessment to research on treatment response. Through his work as an econometrician, Manski shows how statistical imprecision and identification problems affect empirical research in the patient care sphere. In the book, Manski reviews continuing discourse in medicine and critiques how evidence from randomized clinical trials has been used to inform decision making. He describes research on identification, develops decision-theoretic principles for reasonable care under uncertainty, and offers suggestions for sensible decision-making with sample data from randomized trials. Manski ends by reviewing patient care from a public-health perspective and considering management of uncertainty in drug approval. In terms of patient care, Manski seeks to help clinicians, public health planners, and patients recognize and cope with uncertainty when making decisions about patient care"--Provided by publisher